Perlindungan Hukum terhadap Pemenuhan Hak Nafkah Anak Pasca Putusan Pengadilan - Khairunnisyah Khairunnisyah; Maria Rosalina; Sheara Athalia Az Zahra Hasibuan; Nur Rahma Dina (Lembaga Yasin AlSys, 2026)
Divorce in Indonesia continues to leave serious problems in the fulfillment of children’s maintenance rights, although this obligation is normatively attached to the father under Law Number 1 of 1974 and the Compilation of Islamic Law. This condition places children as a vulnerable party to developmental disruptions due to non-compliance with court decisions that have obtained permanent legal force (inkracht van gewijsde). This study aims to analyze the implementation of the fulfillment of children’s maintenance rights after court decisions and to formulate legal protection measures that can be pursued when this obligation is neglected. This study used a normative legal method with statutory, conceptual, and case approaches. Legal materials were analyzed descriptively and analytically through legal interpretation to reveal the gap between das sollen and das sein. The results show a sharp discrepancy in the implementation of child maintenance, because the applicable law enforcement mechanism still tends to be passive and dependent on the mother’s initiative, so court decisions often remain an administrative formality without actual execution. The conclusion of this study affirms that the protection of children’s maintenance rights has not been effective due to the absence of a permanent execution supervisory institution, limited access to the financial data of the obligated party, and weak sanctions for negligent parties. The implications of this study emphasize the need for a paradigm shift from passive enforcement to active enforcement through the integration of inter-institutional data systems, more assertive reform of execution policies, and the strengthening of administrative and criminal sanctions against fathers who neglect maintenance obligations in order to guarantee the best interests of the child.